Analysis and Optimization of Optical Communication Systems According to Transmission Channels - Ozturk, Ibrahim; Unverdi, N. Ozlem (IEEE, 2024)
In this study, wired and wireless optical communication systems were analyzed in detail with OptiSystem 7.0 simulation software. In the wired system, fiber optic cable was utilized, and a free-space optical (FSO) or optical wireless communication (OWC) channel was utilized in the wireless system. Communication channels were created by Wavelength Division Multiplexing (WDM) in both systems. The effect of the pulse generator, modulator, optical amplifier, photodetector, filter, operating wavelength, length of the transmission line, and number of channels on system performance was evaluated. These components and parameters are critical in determining the overall performance of communication systems. System performance was evaluated by the eye diagram and maximum quality factor metrics, which are obtained from the BER (Bit Error Rate) graph and provide information on the reliability and effectiveness of the communication system. This type of analysis plays an important role in the design and optimization of communication systems. The analysis results, which provide important information guiding the design of wired and wireless optical communication systems, are expected to contribute to the development of similar projects in the future.
Keywords: Communication technologies; optical communications; eye diagram; maximum quality factor; optimization; Computer Science; Engineering; Telecommunications